1,2,3-Triazole incorporated coumarin carrying metal-free, Zn(II), Mg(II) phthalocyanines: Synthesis, characterization, theoretical studies, photophysical and photochemical properties - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT; SALAN, ÜMİT (ELSEVIER SCIENCE SA, 2020)
In this study, the preparation of two novel phthalonitrile compounds, 7-(propargyloxy)-3-(3,4-dicyanophenoxyphenyl)coumarin (1), and 7-(propargyloxy)-3-(2,3-dicyanophenoxy-phenyl)coumarin (2) were performed. Two new coumarinyl-1,2,3-triazole hybrids, (1-phenethy1-1H41,2,A-triazole 4 yl) 7 methyleneoxy 3 [F. (3,4 dicya nophenoxy)phenyl]-coumarin (3), and (1-phenethy1-1H-[1,2,3]-triazole 4 yl) 7 methyleneoxy 3 [F. (2,3 dicya nophenoxy)phenyl]-coumarin (4), were synthesized by the copper(I)-catalysed Huisgen 1,3-dipolar cycloaddition reaction of 2-(azidoethyl)benzene with terminal ethynyl bearing coumarin derivatives (1 or 2). These novel phthalonitrile derivatives (3 and 4) were converted into their peripheral (5-7) and non-peripheral (8-10) metal-free, zinc(II) and magnesium(II) phthalocyanine counterparts. The synthesized phthalocyanine derivatives are first examples on the phthalocyanine-coumarin derivatives bearing triazole ring. The structures of all these novel compounds were characterized by variety of spectroscopic techniques including FT-IR, UV-vis, H-1 NMR, MALDI-TOF MS and elemental analysis. The photophysicochemical properties of all studied Pcs (5-10) were determined in dimethyl sulfoxide. The zinc(II) and magnesium(II) phthalocyanines bearing triazole containing coumarin substituents appear to be useful as Type II photosensitizers because the singlet oxygen quantum yields ranged in acceptable values from 0.17 to 0.49 confirmed that these phthalocyanines can be suggested as photosensitizers in Photodynamic Therapy applications. Geometry optimization, frequency analysis and molecular orbital energy values of coumarin/triazole substituted phthalocyanine were performed in Density Functional Theory method using the B3LYP/LANL2DZ level of theory.
Keywords: 1,2,3-Triazole; Phthalocyanine; Coumarin; Click chemistry; PDT; Singlet oxygen; Density functional theory; NONLINEAR-OPTICAL PROPERTIES; DERIVATIVES; ZINC(II); TETRA; ANALOGS; DESIGN